2019
DOI: 10.1093/jn/nxz054
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mean Nutrient Intakes of US Infants, Toddlers, and Young Children from 3 Feeding Infants and Toddlers Studies (FITS)

Abstract: Background Many updates to young child feeding recommendations have been published over the past decade, but concurrent intake trends have not been assessed. Objective The aim of this study was to evaluate adequacy and trends in energy and nutrient intakes of US infants and children aged 0–47.9 mo through use of Feeding Infants and Toddlers Study (FITS) data from 2002, 2008, and 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
(45 reference statements)
4
25
2
Order By: Relevance
“…Our results were based on food and beverage intake and therefore unclear to what extent calcium dietary supplementation impacted overall intake. As stated earlier, the FITS 2016 study found a significant portion of this population did not meet the calcium EAR even when supplement use was taken into consideration [18]; however, no clear age trend was observed in the FITS 2016 data versus our data that included older children and spanned 16 years.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Our results were based on food and beverage intake and therefore unclear to what extent calcium dietary supplementation impacted overall intake. As stated earlier, the FITS 2016 study found a significant portion of this population did not meet the calcium EAR even when supplement use was taken into consideration [18]; however, no clear age trend was observed in the FITS 2016 data versus our data that included older children and spanned 16 years.…”
Section: Discussioncontrasting
confidence: 46%
“…To date only three U.S. studies have assessed the dietary micronutrient intake adequacy in a nationally representative sample of young children. One study reported on children aged 6 to 23 months [ 16 ] and two studies on children from birth to less than 48 months [ 17 , 18 ]. The micronutrient intake in toddler and preschool US children aged 1–6 years has not been previously assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In France, in children who received vitamin D from food sources and supplementation, 10% of infants 30–35 months of age still received less than the recommended intake [67]. In the USA, despite attention to vitamin D supplementation in the last 2 decades, a greater number of children 0–47.9 months of age received less than the recommended supplementation in 2016 compared to 2002 [68]. In the United Kingdom, just over half of parents reported receiving information regarding vitamin D supplementation for their infant and 80% described that they found the information lacking adequate details [69].…”
Section: Recommended Vitamin D Intake For Toddlers Children and Adomentioning
confidence: 99%
“…However, these studies lack recent data and there is limited understanding of population-level changes in food consumption behaviors of young children over time [8]. A more recent analysis using data from the Feeding Infants and Toddlers Study (FITS) examined trends in nutrient intakes among 0–47.9-month-olds and found that nutrient intakes were generally stable from 2002 to 2016; however, sodium intakes exceed recommended levels and there were notable declines in vitamins D and E and fiber among the entire sample and in iron among infants [9].…”
Section: Introductionmentioning
confidence: 99%